Pemberdayaan Kelurahan Dulomo Selatan Melalui Pembuatan APD dan Peningkatan Sistem Imun Dengan Pemberian Multivitamin Pada Penderita PTM Dalam Menghadapi Pandemi Covid-19 - Lusiane Adam; Ahmad Aswad; Ratnawati Ratnawati; Hartati Hartati (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
Covid-19 is an infectious disease caused by a newly discovered type of coronavirus, which spreads very quickly, can attack anyone regardless of age or gender and is more at risk of attacking people with certain medical conditions including sufferers of chronic Non-Communicable Diseases (PTM). The minimum and high cost of PPE, and the high number of PTM sufferers can be at risk of contracting this disease from other people. The purpose of this community service is to empower the community through making PPE to prevent the spread of the Covid-19 virus in the Dulomo Selatan Village community which is the location of the community service. Dulomo Village was chosen as the location for community service because it is one of the working areas of the North City Health Center which has the highest number of elderly people and has the highest number of sufferers of Non-Communicable Diseases. The procedure for the activity is first licensing, coordinating with Dulomo Selatan Village and North City Health Center, preparing tools, health promotion media, and places used for program implementation. This activity consisted of measuring the knowledge of Dulomo Selatan village cadres through distributing questionnaires, counselling about Covid-19, socializing on making simple and fulfilling PPE (masks and face shields), distributing multivitamins for PTM sufferers, and distributing stimulants in the form of masks and hand sanitizers. The results of this community service activity showed that there was an increase in cadres' knowledge about COVID 19, government policies, clean and healthy living behaviour’s and the correct way to use PPE, as well as meeting the needs of PPE in the Dulomo Selatan Village community and especially PTM sufferers in the Dulomo Selatan Village area